On invariant tori of stochastic systems on a plane - Kopas', I. N.; Stanzhitskii, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We study invariant tori of stochastic systems of the ltd type on a plane and present conditions for stability of such sets in probability.